2014
DOI: 10.1371/journal.pone.0088716
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Immune Response in Two MERS-CoV-Infected Patients: Can We Go from Bench to Bedside?

Abstract: One year after the occurrence of the first case of infection by the Middle East Respiratory Syndrome coronavirus (MERS-CoV) there is no clear consensus on the best treatment to propose. The World Health Organization, as well as several other national agencies, are still working on different clinical approaches to implement the most relevant treatment in MERS-CoV infection. We compared innate and adaptive immune responses of two patients infected with MERS-CoV to understand the underlying mechanisms involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
251
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(266 citation statements)
references
References 22 publications
9
251
1
5
Order By: Relevance
“…In view of the high amount of cytokines induced by SARS-CoV, 22,24 MERS-CoV, 25,26 and 2019-nCoV infections, corticosteroids were used frequently for treatment of patients with severe illness, for possible benefit by reducing inflammatory-induced lung injury. However, current evidence in patients with SARS and MERS suggests that receiving corticosteroids did not have an effect on mortality, but rather delayed viral clearance.…”
Section: (39%)mentioning
confidence: 99%
“…In view of the high amount of cytokines induced by SARS-CoV, 22,24 MERS-CoV, 25,26 and 2019-nCoV infections, corticosteroids were used frequently for treatment of patients with severe illness, for possible benefit by reducing inflammatory-induced lung injury. However, current evidence in patients with SARS and MERS suggests that receiving corticosteroids did not have an effect on mortality, but rather delayed viral clearance.…”
Section: (39%)mentioning
confidence: 99%
“…However, a previous study also showed increased levels of interferon-α in a patient who survived MERS-CoV infection but not in a person who died of MERS ( 7 ). Although MERS-CoV evades induction of innate immune responses by cell types, the virus elicits interferon responses in plasmacytoid dendritic cells in vitro ( 8 ).…”
mentioning
confidence: 92%
“…Also, infection triggered significantly higher levels of IP-1o and RANTES than the equivalent dose of SARS-CoV (Zhou et al, 2014). In clinical practice, two MERS patients in France were found to differ in their IFN␣ responses (Faure et al, 2014). Patient 1, who died, did not mount a robust type I IFN response while Patient 2, who survived, did mount a response; particularly notable in Patient 1 was the absence of IFN␣ and comparatively little RIG-I, MDA5, IRF3, IRF7, IL-12 and IFN␥ (Faure et al, 2014).…”
Section: The Immunobiology Of Mers-cov In Tissue and Cell Culturementioning
confidence: 97%
“…MERS-CoV viral RNA detection in serum has proven a useful retrospective source of PCR template when respiratory samples were not available (Hijawi et al, 2013). RNAaemia may also correlate with disease severity; signs of virus cleared from serum in one recovered human case while lingering until the death of another (Faure et al, 2014).…”
Section: Specimen Types and Length Of Viral Sheddingmentioning
confidence: 99%